Disruption of the β1L Isoform of GABP Reverses Glioblastoma Replicative Immortality in a TERT Promoter Mutation-Dependent Manner - Mancini, Andrew (2018)
TERT promoter mutations reactivate telomerase, allowing for indefinite telomere maintenance and enabling cellular immortalization. These mutations specifically recruit the multimeric ETS factor GABP, which can form two functionally independent transcription factor species: a dimer or a tetramer. We show that genetic disruption of GABPβ1L (β1L), a tetramer-forming isoform of GABP that is dispensable for normal development, results in TERT silencing in a TERT promoter mutation-dependent manner. Reducing TERT expression by disrupting β1L culminates in telomere loss and cell death exclusively in TERT promoter mutant cells. Orthotopic xenografting of β1L-reduced, TERT promoter mutant glioblastoma cells rendered lower tumor burden and longer overall survival in mice. These results highlight the critical role of GABPβ1L in enabling immortality in TERT promoter mutant glioblastoma.